Prothrombin Purification by Chromatography - Landaburu, R. H; Albado, Emilia; Santillán, R (Thrombosis and Haemostasis, 1968)
Bovine prothrombin with specific activity above 40,000 u/mg of tyrosine may be obtained by chromatography on Amberlite AG3-X4. The product does not yield autoprothrombin C in appreciable amounts. A fraction separated by this procedure behaves as a procoagulant when replaced into the purified prothrombin.